The Influence of Competence and Physical Work Environment on Teacher Performance - Shanti, Naomi Nirmala; Kamsidik (INTERNATIONAL PENELITI EKONOMI, SOSIAL, DAN TEKNOLOGI, 2025)
This study aims to determine the effect of Competence and Physical Work Environment on Employee Performance at SMK Makarya 1 Jakarta. The sample in this study used a quantitative approach with 40 teachers at SMK Makarya 1 Jakarta as respondents. Data were collected through questionnaires and analyzed using SPSS version 27. Instrument tests (validity and reliability), classical assumption tests (normality, multicollinearity, and heteroscedasticity), and hypothesis tests (partial and simultaneous) were conducted to determine the influence of independent variables on the dependent variable. The results of the analysis showed that all research instruments were declared valid and reliable. The resulting regression model was Y = -2.148 + 0.692 X1 + 0.287 X2. Partially, competence (X1) had a positive and significant effect on teacher performance with a t-count of 7.592 (p < 0.05) and a significance of 0.000. Likewise, the physical work environment (X2) had a positive and significant effect with a t-count of 3.424 (p < 0.05) and a significance of 0.001. Simultaneously, competence and the physical work environment together had a significant effect on teacher performance, indicated by an F-count of 54.542 with a significance of 0.000 (p < 0.05). The two independent variables contributed 74.7% to explaining the variation in teacher performance (R Square = 0.747), while the remaining 25.3% was explained by other factors outside the research model.